2020
DOI: 10.2217/fon-2020-0184
|View full text |Cite
|
Sign up to set email alerts
|

Pembrolizumab Given Concomitantly with Chemoradiation and as Maintenance Therapy for Locally Advanced Head and Neck Squamous Cell Carcinoma: KEYNOTE-412

Abstract: Current treatment guidelines for patients with locally advanced head and neck squamous cell carcinoma (HNSCC) recommend multimodal treatment, including chemoradiation therapy (CRT) or surgery followed by radiation, with or without chemotherapy. The immune checkpoint inhibitor pembrolizumab has previously demonstrated antitumor activity in recurrent and/or metastatic HNSCC in large Phase III trials. For patients with locally advanced disease, Phase Ib data on the use of pembrolizumab in combination with chemora… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
28
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 48 publications
(28 citation statements)
references
References 16 publications
0
28
0
Order By: Relevance
“…Cetuximab, a monoclonal antibody targeting epidermal growth factor receptor, has also been shown to be a tolerated and effective regimen for maintenance therapy in recurrent metastatic HNSCC 43 , 44 . Immune check point inhibitors, such as pembrolizumab for PD-L1 high OSCC, are another type of agents in ongoing clinical trials for maintenance adjuvant therapy in locally advanced HNSCC 45 . For the investigation of the efficacy of these maintenance adjuvant therapies, proper selection of patients at high risk of disease relapse is fundamental in study design.…”
Section: Discussionmentioning
confidence: 99%
“…Cetuximab, a monoclonal antibody targeting epidermal growth factor receptor, has also been shown to be a tolerated and effective regimen for maintenance therapy in recurrent metastatic HNSCC 43 , 44 . Immune check point inhibitors, such as pembrolizumab for PD-L1 high OSCC, are another type of agents in ongoing clinical trials for maintenance adjuvant therapy in locally advanced HNSCC 45 . For the investigation of the efficacy of these maintenance adjuvant therapies, proper selection of patients at high risk of disease relapse is fundamental in study design.…”
Section: Discussionmentioning
confidence: 99%
“…The primary hypothesis is that Pembrolizumab given in combination with SoC CRT is superior in event-free survival (disease progression or death in a maximum time frame of five years) than the SoC CRT. The investigators plan to complete the study by 2023 and believe that this trial may elucidate Pembrolizumab’s role when added to SoC in patients for whom five-year survival rates are poor, besides gaining insight on factors that influence the efficacy of immunotherapy by studying biomarkers data [ 98 ].…”
Section: Immune Checkpoint Blockade (Icb) In Hnscc Treatmentmentioning
confidence: 99%
“…In terms of LA disease, a phase Ib study with 59 patients assessed pembrolizumab with weekly cisplatin-based CRT and demonstrated a favorable toxicity profile, with an end of treatment complete response of 85.3% and 78.3% based on imaging in HPV positive and negative groups, respectively [ 91 ]. Currently, a phase III trial KEYNOTE-412 is ongoing and is assessing pembrolizumab with CRT in LA SCCHN (NCT03040999) [ 92 ]. In addition, a trial assessing dual ICI blockade with RT in LA SCCHN is actively recruiting patients (NCT03426657).…”
Section: Current Applications Of Egfr Inhibition In Scchn In the Era Of Immunotherapymentioning
confidence: 99%